Facebook Powered Measurement and Evaluation for Iron Folic Acid Health Intervention in India [version 2; peer review: 2 approved] - Drew Bernard; Chris McCullough; Sarah Francis; Avery Holton; Nadia Diamond-Smith (Gates Open Research, 2019)
As the media landscape changes and billions of people around the world turn to Facebook, Instagram, WhatsApp, and other social media platforms for information and social interactions, the need to develop effective methods of leveraging social media for social behavior change communication (SBCC) becomes increasingly important. Yet, in order for the public health sector to embrace social media for SBCC, we must have methods for measuring the impact of social media-based SBCC. In this letter, we share a new approach for measurement and evaluation of social media-based SBCC campaigns. The approach was developed as part of an iron-folic acid health intervention targeting young women in two states in northern India; Uttar Pradesh and Maydar Pradesh.